Sharia Principles on Information Technology-Based Financing Services - Trisadini Prasastinah Usanti; Prawitra Thalib; Nur Utari Setiawati (Yuridika, 2019)
The Financial Services Authority only regulates information technology-based money lending and borrowing services that have not yet regulated sharia-based information technology financing services (fintech Syariah). This is evidenced by the provision of loan interest rates in the Financial Services Authority Regulation. This is contrary to sharia principles. The existence of Fintech Syariah is only based on DSN-MUI Fatwa Number 117/DSN-MUI/II/2018 which expressly states that information technology-based financing services are permitted with conditions that must be by sharia principles so that they cannot promise usury, gharar, maysir, tadlis, and dharar. Contracts that frame the legal relationship between the organizer, the financing provider and the recipient of financing, among others, the contract of wakalah bil ujrah, mudharabah, musyarakah, ijarah, and murabahah